2015
DOI: 10.1021/acs.est.5b02473
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Pattern Changes of Short- and Medium-Chain Chlorinated Paraffins in Marine Mammals from the South China Sea over the Past Decade

Abstract: Temporal trends of short-(SCCPs) and medium-chain chlorinated paraffins (MCCPs) were examined in blubber samples of 50 finless porpoises (Neophocaena phocaenoides) and 25 Indo-Pacific humpback dolphins (Sousa chinensis) collected from the South China Sea between 2004 and 2014. Elevated levels of SCCPs and MCCPs were detected in all blubber samples of both cetacean species. Concentrations of SCCPs ranged from 280 to 3900 ng·g −1 dry weight (dw) in porpoises and from 430 to 9100 ng·g −1 dw in dolphins, while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
73
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 41 publications
16
73
5
Order By: Relevance
“…Regarding the chlorine content, Cl 7 and Cl 8 were the dominant congeners with the average percentages ranging from 25%-30% (27%, average) and from 21%-33% (26%, average) of the total SCCPs, respectively. This patterns of SCCPs were generally consistent with those in Indo-Pacific humpback dolphins from the study region in recent years (2012)(2013)(2014) (Zeng et al, 2015); but different from those reported in the surface sediment samples with higher abundance of short carbon chain (C 10 and C 11 ) in the Pearl River Estuary, although homologue groups with 7-8 chlorines dominated in the sediments (Chen et al, 2011). However, it was not clear whether this finding suggested selective accumulation of longer carbon chain SCCPs in these organisms; because Zeng et al (2015) found a more significant temporal shift trend in the SCCP homologue pattern from shorter-to longer-chain groups in dolphin from the Pearl River Estuary between 2004 and 2014.…”
Section: Homologue Patterns In Marine Speciessupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the chlorine content, Cl 7 and Cl 8 were the dominant congeners with the average percentages ranging from 25%-30% (27%, average) and from 21%-33% (26%, average) of the total SCCPs, respectively. This patterns of SCCPs were generally consistent with those in Indo-Pacific humpback dolphins from the study region in recent years (2012)(2013)(2014) (Zeng et al, 2015); but different from those reported in the surface sediment samples with higher abundance of short carbon chain (C 10 and C 11 ) in the Pearl River Estuary, although homologue groups with 7-8 chlorines dominated in the sediments (Chen et al, 2011). However, it was not clear whether this finding suggested selective accumulation of longer carbon chain SCCPs in these organisms; because Zeng et al (2015) found a more significant temporal shift trend in the SCCP homologue pattern from shorter-to longer-chain groups in dolphin from the Pearl River Estuary between 2004 and 2014.…”
Section: Homologue Patterns In Marine Speciessupporting
confidence: 85%
“…A more recent study of SCCPs in Indo-Pacific humpback dolphin (Sousa chinensis) was conducted by Zeng et al (2015) in the Pearl River Estuary, and the measured ∑ SCCP concentrations in blubber samples ranged from 920 and 24,000 ng·g −1 lw with a mean value of 5500 ng·g −1 lw, which were higher than those detected in this study (210-21,000 ng·g −1 ). The levels of ∑ SCCPs in the dorsal muscle of fish species (210-2800 ng·g − 1 lw and 5.3-58 ng·g −1 wet weight, ww) from the Pearl River Estuary were higher than the concentrations reported for top predatory fish (2-10 ng·g −1 ww in the whole body homogenates) in Canada (Basconcillo et al, 2015), but lower than those in the muscles of marine fish from Liaodong Bay of North China (9700-33,000 ng·g − 1 lw) (Ma et al, 2014b), and marine fish (33-140 ng·g − 1 ww) from Ebro River Delta in Spain (Parera et al, 2013).…”
Section: Sccps Levels In Marine Speciescontrasting
confidence: 74%
See 1 more Smart Citation
“…SCCPs are primarily released into the environment from anthropogenic sources as a type of high production volume chemical and are detected in the different environmental matrices, including air, water, sediments and biota (Barber et al, 2005;Bayen et al, 2006;Coelhan, 2010;Fridén et al, 2011;Marvin et al, 2003;Thomas et al, 2006;Zeng et al, 2015). The SCCPs travel to polar regions in a three-step process: release, transport and deposition (Wania, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, CPs may also enter the environment through waste incineration (Feo et al, 2009), sewage treatment (Zeng et al, 2012b) and e-waste dismantling (Lu et al, 2015). Up to now, CPs have been found to be widespread in the air , water (Coelhan, 2010), soil (Wang et al, 2014), sediment (Zeng et al, 2013), aquatic and terrestrial wildlife (Reth et al, 2006;Zeng et al, 2015), and even in human breast milk . So it's important to improve our understanding of the pollution status and potential risks posed by CPs.…”
Section: Introductionmentioning
confidence: 99%